Nutrient Deprivation Mobilizes the Production of Unique Tocopherols as a Stress-Promoting Response in a New Indigenous Isolate Monoraphidium sp. - Singh, Rabinder; Paliwal, Chetan; Nesamma, Asha A.; Narula, Alka; Jutur, Pannaga P. (Frontiers in Marine Science, 2020)
The economic feasibility of the next-generation algal biofuels rely largely on the simultaneous production of high-value-added bioproducts (HVABs) in these photosynthetic cell factories. In this study, a newly isolated indigenous microalga belonging to the selenastraceae family Monoraphidium sp. (designated as CABeR41) has been isolated and characterized for its relevant biofuel precursors along with other HVABs, i.e., tocopherols. Our preliminary data sets demonstrate accumulation of higher amounts of lipids (266.6 mg g–1 dcw) along with antioxidant molecules, such as α- and δ-tocopherols (456 μg g–1 dcw and 974 μg g–1 dcw), simultaneously when subjected to nutrient deprivation. The total tocopherol content has been increased in nitrogen-deplete conditions to 1450.24 μg g–1 dcw from 638.2 μg g–1 dcw. In conclusion, bioprospecting of new isolates from natural habitats and fine-tuning of specific conditions without compromising growth has potential for developing into a sustainable industrial strain for concomitant production of biofuels and bioproducts.